Alternative approaches to news: The role of media distrust, perceived network homophily, and interests in news topics - Segado-Boj, Francisco; Said-Hung, Elías Manuel (Revista de Comunicacion, 2022)
This study focuses on three contemporary alternative users’ attitudes to news previously detetected in the literature: ‘News finds me’, ‘The information is out there’ and ‘I don’t know what to be-lieve. It analyzes the role of users’ media distrust and social network homophily perception as predictors of each considered attitude. Secondly, the study also considers the effect of the mentioned attitude on user’s interests in different news topics. Last, it compares the reciprocal influence of the aforementioned attitudes among them. A survey (n = 279) was developed among Spanish Facebook users. Data was analysed through multiple regression test. Results show that media distrust positively predicted “The Information Is Out There” but was not relevant in the cases of “News Finds Me” and “I Don’t Know What To Believe”. “News Finds Me” negatively predicted interest in hard news (domestic, international poli-tics, and economy), and “The Information Is Out There” predicted interest in lifestyle news and stories about celebrities. Perceived network homophily was not predicted by any of the observed attitudes. A reciprocal influence was detected between “The Information Is Out There” and “News Finds Me” but no influence was identified from or to “I Don’t Know What To Believe”. We conclude that “The Information Is Out There” may have the same negative effects on political knowledge and participation that “News Finds Me” as it drives users away from hard news item and towards softer topics.
Rutas alternativas a las noticias: Desconfianza en medios, homofilia percibida e interés en temas
Este estudio se centra en tres actitudes alternativas al consumo tradicional de noticias de-finidas previamente en las noticias: “Las noticias me encuentran”, “La información está ahí fuera” y “No sé Qué Creer”. Analiza el papel de la desconfianza de los usuarios respecto a los medios y la homofilia percibida de los contactos en sus redes sociales como predictores de cada una de estas actitudes. Por último, compara la influencia recíproca de las mencionadas actitudes entre sí. Los datos se extrajeron de una encuesta (n = 279) entre usuarios españoles de Facebook y se analizaron mediante pruebas de re-gresión lineal múltiple. Los resultados muestran que la desconfianza en los medios predijo positivamente “La información está ahí fuera” pero no resultó relevante en los casos de “Las noticias me encuentran” ni “No sé qué creer”. “Las Noticias Me Encuentran” predijo negativamente el interés en las noticias duras (política nacional, internacional y economía) y “La información está ahí fuera” predijo el interés en noticas de estilo de vida y sobre famosos. La homofilia percibida de la red no predijo ninguna de las actitudes observadas. Se detectó una influencia recíproca entre “La Información Está Ahí Fuera” y “Las noticias me encuentran” pero no respecto a “No sé qué creer”. Concluimos que “La Información Está Ahí Fuera” puede causar los mismos efectos negativos en la participación y conocimiento sobre política que “Las noticias me encuentran” en tanto que deriva a los usuarios de noticias duras hacia temas más blandos.
Keywords: hard news; media distrust; news users; perceived network homophily; soft news; usuarios; noticias duras; noticias blandas; desconfianza mediática; homofilia percibida de la red; Scopus